Intranuclear Delivery of HIF-1α-TMD Alleviates EAE via Functional Conversion of TH17 Cells - Shin, Jin-Su; Kim, Ilkoo; Moon, Jae-Seung; Ho, Chun-Chang; Choi, Min-Sun; Ghosh, Sankar; Lee, Sang-Kyou (Frontiers in Immunology, 2021)
TH17 cells are involved in several autoimmune diseases such as multiple sclerosis (MS) and rheumatoid arthritis (RA). In addition to ROR-γt, HIF-1α is essential for the differentiation and inflammatory function of TH17 cells. To investigate the roles of HIF-1α in the functional regulation of TH17 cells under the normal physiological condition without genetic modification, the nucleus-transducible form of transcription modulation domain (TMD) of HIF-1α (ntHIF-1α-TMD) was generated by conjugating HIF-1α-TMD to Hph-1 protein transduction domain (PTD). ntHIF-1α-TMD was effectively delivered into the nucleus of T cells without cellular cytotoxicity. ntHIF-1α-TMD significantly blocked the differentiation of naïve T cells into TH17 cells in a dose-dependent manner via IL-17A and ROR-γt expression inhibition. However, T cell activation events such as induction of CD69, CD25, and IL-2 and the differentiation potential of naïve T cells into TH1, TH2, or Treg cells were not affected by ntHIF-1α-TMD. Interestingly, TH17 cells differentiated from naïve T cells in the presence of ntHIF-1α-TMD showed a substantial level of suppressive activity toward the activated T cells, and the increase of Foxp3 and IL-10 expression was detected in these TH17 cells. When mRNA expression pattern was compared between TH17 cells and ntHIF-1α-TMD-treated TH17 cells, the expression of the genes involved in differentiation and functions of TH17 cells was down-regulated, and that of the genes necessary for immune-suppressive functions of Treg cells was up-regulated. When the mice with Experimental Autoimmune Encephalomyelitis (EAE) were treated with ntHIF-1α-TMD with anti-IL-17A mAb as a positive control, the therapeutic efficacy of ntHIF-1α-TMD in vivo was comparable to that of anti-IL-17A mAb, and ntHIF-1α-TMD-mediated therapeutic effect was contributed by the functional conversion of TH17 cells into immune-suppressive T cells. The results in this study demonstrate that ntHIF-1α-TMD can be a new therapeutic reagent for the treatment of various autoimmune diseases in which TH17 cells are dominant and pathogenic T cells.